Konsep Pendidikan Islam Menurut Imam Nawawi - Husaini, Husaini (Jurnal Ikhtibar Nusantara, 2023)
Islamic education according to Imam Nawawi contains profound principles, including sincere intentions for the sake of Allah, good ethics, and avoiding spiritual diseases. A teacher must have pure intentions, teach without seeking worldly gains, and maintain integrity in teaching. This study aims to examine the concept of Islamic education according to Imam Nawawi. The research method employed is literature review. The study found that Imam Nawawi emphasizes the importance of integrity, sincere intentions, good ethics, and purity of heart for a teacher in carrying out their teaching duties. A teacher must have Sincere Teaching Intentions, Maintain Good Ethics, Avoid Spiritual Diseases, and Honor Knowledge and Prioritize Trust and Prayer. By adhering to these principles, a teacher can uphold the honor and quality of teaching, build healthy relationships with their students, and create a positive and conducive learning environment for the holistic development of students.